2016
DOI: 10.1177/1526602816633705
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Flushing Technique to Prevent Cerebral Arterial Air Embolism and Stroke During TEVAR

Abstract: Arterial air embolism is a potentially underappreciated problem of aortic endografting, especially in the proximal segments of the aorta. CO2 flushing may have the potential to reduce air embolization during TEVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 14 publications
1
57
0
3
Order By: Relevance
“…193 To minimize the risk of stroke, temporary carotid artery occlusion, filter placement and carbon dioxide flushing of the delivery system have been proposed. 193,194,200 For endovascular aortic arch repair, there are 2 general graft designs: fenestrated and branched arch endografts. Both designs are currently available as custom-made devices only, so a manufacturing time of between 4 and 8 weeks precludes their use in urgent and emergency situations.…”
Section: Classmentioning
confidence: 99%
“…193 To minimize the risk of stroke, temporary carotid artery occlusion, filter placement and carbon dioxide flushing of the delivery system have been proposed. 193,194,200 For endovascular aortic arch repair, there are 2 general graft designs: fenestrated and branched arch endografts. Both designs are currently available as custom-made devices only, so a manufacturing time of between 4 and 8 weeks precludes their use in urgent and emergency situations.…”
Section: Classmentioning
confidence: 99%
“…This patient is part of our earliest experience, when device flushing with carbon dioxide was not routinely performed. Kölbel and co-authors reported in a group of 36 patients treated with ascending aorta or arch devices flushed with carbon dioxide, just one minor stroke in a patient with a highly calcified aortic arch (6). Of course, our sample is too small to reach statistical significance in determining the use of carbon dioxide as a protective factor in the prevention of air embolism-related neurologic events.…”
Section: Discussionmentioning
confidence: 76%
“…All patients received a LCCA-LSA bypass as first step. Endovascular step was carried out after a mean interval of 7 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] days. The LSA stump was always occluded by a vascular plug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Prävention eines perioperativen Schlaganfalls bei TEVAR, insbesondere bei weit in den Aortenbogen hineinreichenden Rekonstruktionen, steht ebenfalls besonders im Fokus. Das Risiko von Mikroembolien während der Manipulation im Aortenbogen, vor allem bei hoher Thrombuslast der Aorta (shaggy aorta) [15], aber auch das technisch bedingte Risiko von Luftembolien während der Freisetzung der Endoprothese, sind pathophysiologische Mechanismen, die primär für die Entstehung von Schlaganfällen verantwortlich sind [16]. Die Erfassung perioperativer Schlaganfälle in TE-VAR-Studien sowie die Etablierung von Techniken zur ▶ Abb.…”
Section: Tevar-planungunclassified